Modelagem numérica da influência do eletrojato equatorial em dados magnetotelúricos produzidos por estruturas tridimensionais - GONZÁLEZ CARRASQUILLA, Antonio Abel (Universidade Federal do Pará, 2014)
South America presents several unique geomagnetic features, one of which is the Equatorial Electrojet, a current system which extends east - west in Northern Brazil, for almost 3500 km. Considering the fact that the influence of the Equatorial Electrojet can be detected at great distances from its central axis, it is important to understand its effects on magnetotelluric exploration in Brazil. In magnetotelluric prospecting, the influence of the equatorial electrojet has been modelled for both one and two - dimensional geological media, employing both analytical and numerical techniques solutions such as finite element and finite difference. Three-dimensional geological media have been modeled by "thin – layers "using a "thin sheet" algorithm. Lines of current, gaussian electrojets and undulatory electrojets have been used as induction sources to simulate the equatorial electrojet in these algorithms. In this thesis the principal objective is to model the effects of the equatorial electrojet on three - dimensional structures commonly found in geophysical prospecting. To accomplish this, we have computed numerical solutions of the integral equation for three - dimensional media using the inductive sources mentioned before. As previous works have indicated, our results also show that the influence of the equatorial electrojet is prominant only for frequencies lower than 10-1 Hz. This influence decreases with distance but is detectable up to as far as 3000 km from the center of the electrojet. Thus, the presence of peaks in the apparent resistivity profiles over a homogeneous half - space indicates that the influence of the electrojet is more noticeable for this kind of medium. These peaks display different amplitudes for each type of simulated electrojet, and the peak locations also change from one electrojet to the other. However, when we use more geologically realistic one - dimensional models such as a stratified media, the effect of the electrojet source diminishes considerably and the results do not vary greatly for the different kinds of electrojet employed in the model. This effect is caused by the electromagnetic energy dissipation due to the presence of stratified conductive layers within the media. Within the 3000 km region, the three - dimensional electromagnetic response can be larger or smaller than the plane wave response, depending on location body, frequency, kind of the electrojet and geology. When the apparent resistivity is larger than the plane wave response, there is a spread between the one and the three-dimensional sounding curves caused by the electrojet, as well as a widening of the profile anomaly caused by the three - dimensional inhomogeneities relative to the one due to a plane wave. When the apparent resistivity is less the two kinds of sources yield anomalies approximately equal as well as a shortening of the profile anomaly. On the other hand, the phase usually shows an inverted way related to the apparent resistivity. This means that when one phase goes up the apparent resistivity goes down, and vice - versa. Similarily at high frequencies, the one and three - dimensional phases are offset, while at low frequencies they are the same, except for the undulating electrojet with undulation factor α = -2 and -3. Our results also show that the geometric characteristics of three-dimensional structures, such as their orientation relative to the direction of the electrojet and the dimensions of their principal direction, change the response due to the electrojet source as compared to a plane wave source. For example, when the three - dimensional structure is rotated 90 degrees, relative to the direction of the electrojet, there is a change in polarization (of the electric and magnetic fields) but there are no changes in the values of apparent resistivity at the center of symmetry of the structure. When the measurements are taken away from the center of symmetry changes in the apparent resistivity are shown when compared with the unrotated structure. This is due to the persistente of the galvanic effects at the center of the structure and the presence of inductive effects at the periphery of the three - dimensional body. When we elongate the principal direction of the three - dimensional structure, the magnetotelluric soundings start to approach those of two-dimensional structures. This is more noticiable in the XY polarization. Even so, the responses of the models tested are still quite different from the responses of the quasi two - dimensional structures. Nevertheless, the effects of the electrojet in structures with elongated principal direction are very similar to those present in smaller structures, considering the differences between the soundings of both kinds of structures. On the other hand, the apparent resistivities of this kind of elongated structures show a great increase at the edges of these structures, both for the plane wave or electrojet sources. This effect is caused by the chanelling of the current along the main direction of the structure. The modelling of gelogical structures in the Marajó Basin, confirms that the effects of the electrojet can be detected even in small horst and graben structures located at great distances from electrojet center. Electrojet effects are noticeable in both one and three - dimensional media for two frequency bands, one near 10-1 Hz and another band, between 10-3 Hz to DC. This possibly reflects the influence of a resistive geological basement and a resistive lower crust, respectively. The results of the analysis, using the electrojet as an inductive source show that at low frequencies the computed responses from the magnetotelluric soundings can be strongly distorted, both by galvanic effects in the three - dimensional structure as well as the presence of the electrojet. Therefore, if the equatorial electrojet effects are not accounted for, a misleading interpretation magnetotelluric data will result. Similarily, a three - dimensional model should be used to interpret the data, instead of one-dimensional Tikhonov-Cagniard model.